Nonlocal study of the near field radiative heat transfer between two n-doped semiconductors. (November 2015) - Singer, F.; Ezzahri, Y.; Joulain, K.
Highlights: Lindhard–Mermin nonlocal model is proposed for highly doped semi-conductors. The radiative heat transfer (RHT) between two parallel n-Si planes is calculated. The near-field RHT saturates as the separation distance is reduced. The saturation is in contrary with the local near-field RHT calculations. Abstract: We study in this work the near-field radiative heat transfer between two semi-infinite parallel planes of highly n-doped semiconductors. Using a nonlocal model of the dielectric permittivity, usually used for the case of metallic planes, we show that the radiative heat transfer coefficient saturates as the separation distance is reduced for high doping concentration. These results replace the 1/ d 2 infinite divergence obtained in the local model case. Different features of the obtained results are shown to relate physically to the parameters of the materials, mainly the doping concentration and the plasmon frequency.